2021
DOI: 10.1136/annrheumdis-2021-221036
|View full text |Cite
|
Sign up to set email alerts
|

Analysing cord blood levels of TNF inhibitors to validate the EULAR points to consider for TNF inhibitor use during pregnancy

Abstract: BackgroundTo minimise placental transfer of tumour necrosis factor inhibitors (TNFi), the European League Against Rheumatism (EULAR) created points to consider (PtC) for the use of TNFi during pregnancy. We are the first to validate the EULAR-PtC by analysing TNFi concentrations in cord blood.MethodsPatients were derived from the Preconceptional Counselling in Active Rheumatoid Arthritis Study. TNFi was stopped at the time points recommended by the EULAR. Maternal blood and cord blood were collected and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
14
0
4
Order By: Relevance
“…Etanercept is known to cross the placental barrier, being detected in the serum of children born from patients treated with etanercept during pregnancy (Berthelsen et al, 2010). However, a recent studied reported that etanercept was not detectable in cord blood sample, whereas others TNF-α inhibitors were detectable, including adalimumab and infliximab (Ghalandari et al, 2021). Therefore, one possibility is that TNFα inhibition may be impacting on placentation.…”
Section: Discussionmentioning
confidence: 99%
“…Etanercept is known to cross the placental barrier, being detected in the serum of children born from patients treated with etanercept during pregnancy (Berthelsen et al, 2010). However, a recent studied reported that etanercept was not detectable in cord blood sample, whereas others TNF-α inhibitors were detectable, including adalimumab and infliximab (Ghalandari et al, 2021). Therefore, one possibility is that TNFα inhibition may be impacting on placentation.…”
Section: Discussionmentioning
confidence: 99%
“…6 , 7 , 8 , 9 Among these, CZP crosses the placenta in very scarce amounts due to the lack of the Fc part. 10 Data from more than 500 prospectively followed pregnancies exposed to CZP did not indicate higher rates of congenital malformations (CMs) compared to the general population. CZP is generally considered to be safe for use during pregnancy.…”
Section: Introductionmentioning
confidence: 96%
“…The last American College of Rheumatology (ACR) guidelines are in line with those issued by the EULAR [ 14 ]. It was subsequently confirmed that discontinuing TNFi treatment at the recommended time points resulted in undetectable or low cord blood levels of TNFi [ 24 ]. Furthermore, no signal for adverse pregnancy outcomes or congenital malformations was observed in CZP-exposed pregnancies documented in a large post-marketing pharmacovigilance database [ 25 ].…”
Section: Introductionmentioning
confidence: 99%